2021
DOI: 10.1155/2021/6073757
|View full text |Cite|
|
Sign up to set email alerts
|

Medical Imaging Diagnosis of Anterior Cruciate Ligament Injury Based on Intelligent Finite-Element Algorithm

Abstract: A medical imaging method based on an intelligent finite-element algorithm was proposed to diagnose anterior cruciate ligament injury modeling better. CT three-dimensional finite-element modeling was used to predict the fixation points of the anterior cruciate ligament (ACL) femoral tunnel. In this study, 19 subjects were selected, including 11 males and 8 females. There were seven cases of the left knee and 12 cases of the right knee; all patients had sports injuries. The anatomical structure of a patient’s kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Since the knee is a bilateral organ, and when evaluating the most affected side the results showed that the right knee is the most affected side with a frequency of 50 patients (Table 4). Wang (2021), [11], got a similar finding, there were seven cases of the left knee and 12 cases of the right knee; all patients had sports injuries.…”
Section: Resultsmentioning
confidence: 63%
“…Since the knee is a bilateral organ, and when evaluating the most affected side the results showed that the right knee is the most affected side with a frequency of 50 patients (Table 4). Wang (2021), [11], got a similar finding, there were seven cases of the left knee and 12 cases of the right knee; all patients had sports injuries.…”
Section: Resultsmentioning
confidence: 63%
“…Some researchers placed external reference points on the knee joint of volunteers to match CT and MRI images and then combined different structures of the knee joint by anatomy. 12 Most tissue models need to be manually outlined on the images by professionals using image processing software such as Mimics, 13 then imported into finite element analysis software such as ABAQUS and MARC for calculation. 14 In this analysis and calculation process, parameters such as displacement and stress can be obtained (Figure 3).…”
Section: Modeling Toolsmentioning
confidence: 99%
“…Most tissue models need to be manually outlined on the images by professionals using image processing software such as Mimics, 13 then imported into finite element analysis software such as ABAQUS and MARC for calculation 14 . In this analysis and calculation process, parameters such as displacement and stress can be obtained (Figure 3).…”
Section: Model Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%